Interleukin-37: A crucial cytokine with multiple roles in disease and potentially clinical therapy - Wang, Lijuan (Oncol Lett, 2018)
Interleukin (IL)-37, a new IL-1 family member, has received increasing attention in recent years. In the past decade, it has been determined that IL-37 is expressed in various normal cells and tissues and is regulated by inflammatory stimuli and pro-cytokines via different signal transduction pathways. Recently, it has been found that IL-37 is expressed in a variety of cancers, chronic inflammatory and autoimmune disorders, and exerts anti-inflammatory effects. Moreover, a growing body of literature demonstrates that IL-37 plays a vital role in inhibiting both innate and adaptive immune responses as well as inflammatory reactions. In addition, IL-37 may prove to be a new and potentially useful target for effective cytokine therapy. Further evidence is needed to clarify in more detail the effects of IL-37 in experimental and clinical studies. Based on an extensive summary of published data, the aim of this review is to outline the current knowledge of IL-37, including the location, structure, expression, regulation and function, as well as the potential clinical applications of this cytokine.